The hexosamine signaling pathway: O-GlcNAc cycling in feast or famine - Hanover, John A.; Krause, Michael W.; Love, Dona C. (Biochimica et biophysica acta, 2010)
The enzymes of O-GlcNAc cycling couple the nutrient-dependent synthesis of UDP-GlcNAc to O-GlcNAc modification of Ser/Thr residues of key nuclear and cytoplasmic targets. This series of reactions culminating in O-GlcNAcylation of targets has been termed the hexosamine signaling pathway (HSP). The evolutionarily ancient enzymes of O-GlcNAc cycling have co-evolved with other signaling effecter molecules; they are recruited to their targets by many of the same mechanisms used to organize canonic kinase-dependent signaling pathways. This co-recruitment of the enzymes of O-GlcNAc cycling drives a binary switch impacting pathways of anabolism and growth (nutrient uptake) and catabolic pathways (nutrient sparing and salvage). The hexosamine signaling pathway (HSP) has thus emerged as a versatile cellular regulator modulating numerous cellular signaling cascades influencing growth, metabolism, cellular stress, circadian rhythm, and host–pathogen interactions. In mammals, the nutrient-sensing HSP has been harnessed to regulate such cell-specific functions as neutrophil migration, and activation of B-cells and T-cells. This review summarizes the diverse approaches being used to examine O-GlcNAc cycling. It will emphasize the impact O-GlcNAcylation has upon signaling pathways that may be become deregulated in diseases of the immune system, diabetes mellitus, cancer, cardiovascular disease, and neurodegenerative diseases.